Mating System and Effective Population Size of the Overexploited Neotropical Tree (Myroxylon peruiferum L.f.) and Their Impact on Seedling Production. (10th November 2017) - Silvestre, Ellida de Aguiar; Schwarcz, Kaiser Dias; Grando, Carolina; de Campos, Jaqueline Bueno; Sujii, Patricia Sanae; Tambarussi, Evandro Vagner; Macrini, Camila Menezes Trindade; Pinheiro, José Baldin; Brancalion, Pedro Henrique Santin; Zucchi, Maria Imaculada
Abstract: The reproductive system of a tree species has substantial impact on genetic diversity and structure within and among natural populations. Such information, should be considered when planning tree planting for forest restoration. Here, we describe the mating system and genetic diversity of an overexploited Neotropical tree, Myroxylon peruiferum L.f. (Fabaceae) sampled from a forest remnant (10 seed trees and 200 seeds) and assess whether the effective population size of nursery-grown seedlings (148 seedlings) is sufficient to prevent inbreeding depression in reintroduced populations. Genetic analyses were performed based on 8 microsatellite loci. M. peruiferum presented a mixed mating system with evidence of biparental inbreeding (t ^ m − t ^ s = 0.118). We found low levels of genetic diversity for M. peruiferum species (allelic richness: 1.40 to 4.82; expected heterozygosity: 0.29 to 0.52). Based on N e ( v ) within progeny, we suggest a sample size of 47 seed trees to achieve an effective population size of 100. The effective population sizes for the nursery-grown seedlings were much smaller N e = 27.54–34.86) than that recommended for short term N e ≥ 100) population conservation. Therefore, to obtain a reasonable genetic representation of native tree species and prevent problems associated with inbreeding depression, seedling production for restoration purposes may require a much larger sampling effort than is currently used, a problem that is further complicated by species with a mixed mating system. This study emphasizes the need to integrate species reproductive biology into seedling production programs and connect conservation genetics with ecological restoration.